editorial board - Srinakharinwirot Research; Development (Journal of Humanities; Social Sciences) (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
Srinakharinwirot Research and Development (Journal of Humanities and Social Sciences)